Comparison of Multicultural Education in SMP Maria Immaculata Y ogyakarta and SMP 5 Yogyakarta - Taat Wulandari (LPPM UNY, 2013)
This study aims to describe the ideas of multicultural education from principals, teachers, students, and students' parents. Their ideas and under standings are explored to obtain a description of practices by principals, teachers, students, and students' parents to implement multicultural education in the school life. This study employed the qualitative method. It used the naturalistic inquiry. The research subjects comprised principals, teachers, students, and students' parents in SMP Maria Immaculata Yogyakarta and SMP 5 Yogyakarta. They were selected by means of the purposive and snowball sampling techniques. The data were collected by means of three techniques, namely observation, interview, and documentation techniques. The research instrument was the researcher herself. The data trustworthiness was enhanced through the triangulation technique, including source and data triangulations. The data were analyzed using the qualitative data analysis by Miles Huberman, consisting of data reduction, data display, and conclusion drawing. After the investigation of the life in the two schools, the following conclusions are drawn. 1) Principals, teachers, students, and students' parents have awareness and understanding of individual differences. 2) The conceptualization of the awareness is manifested in the values to develop, namely no discrimination, understanding of other people's perceptions, avoidance of stereotypes, attempts for equality, realization of justice, mutual acceptance, mutual respect, mutual tolerance, empathy, communication, affection, family atmosphere, brotherhood, and tolerance.